Assessing the viability of a grid-connected PV power plant in Mubi, Adamawa State, Nigeria - Luqman, Raji; Kehinde Issa, Abdul-Jeleel; Owolabi, Abdulhameed Babatunde; Yakub, Abdulfatai Olatunji; Same, Noel Ngando; Yahaya, Abdullahi; Yasin, Naveed; Kavgic, Miroslava; Suh, Dongjun; Huh, Jeung-Soo (Frontiers in Energy Research, 2023)
This paper is based on a techno-economic analysis and environmental impact of a proposed 1MW solar photovoltaic (PV) power plant at the Federal Polytechnic Mubi (FPM) main campus in Northeast Nigeria. Photovoltaic power plant converts solar radiation into electricity which can be used as a source of electrical power for appliances at homes and equipment at any tertiary institution to meet their daily energy requirement. RETScreen Expert Software was used to evaluate the techno-economic and environmental sustainability of installing a grid-connect solar PV power plant. The research results revealed the annual solar radiation of 5.74kWh/m2/day; the maximum annual energy production was estimated to be 1,550.98MWh. It was discovered that March yielded maximum energy production of 146.89MWh than other months in a year. The project profitability and economic sustainability were determined with a good Internal Rate of Return (IRR) of 11.9% and a positive Net Present Value (NPV) of 681,164. The proposed solar PV power plant has a simple payback period of 11.4 years. The maximum Greenhouse Gas (GHG) emission reduction is 670.9tCO2, equivalent to 61.7 hectares of forest absorbing carbon.